On small motions of a “liquid-gas” system in a bounded domain - Vronskii, B. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study small motions and free oscillations of a compressible stratified liquid, the structure of the spectrum, and the basis property of a system of eigenvectors and obtain asymptotic relations for eigenvalues.